A Preliminary Note on the Identity of the Controversial Mikania - Vaid, K. M. (Indian Forester, 1973)
Mikania is a very troublesome climber in forests of eastern India. Our century-old classical works on Indian botany recognised this species as Mikania scandens (L.) Willd. and this name remained current till very recently. Subsequently, its nomenclatural status was given more attention and the name was changed to M. cordata (Burm. f.) B.L. Robinson syn. M. scandens cl non Willd. on the plea that the former is a North American species and the latter alone Is found In East Asia. However, several collections received recently for determination have revealed that a species which Is most common in the Indian region is M. micrantha H.B.K. which had hitherto been never 'known' from this region or by this name. A retrograde check up on the old collections of M. cordata bas shown that there Is possibility of an 'error' In their earlier determinations and almost all such specimens are of M. micrantha, which is otherwise, of south American origin and also well known in the West ladies. Futther investigation is in progress to ascertain whether M. cordata syn. M. scandens really occurs In India or the plant has all along been going by a false name.